Hubungan Sisa Makanan Pasien Berdasarkan Cita Rasa Makanan dan Penampilan Makanan di Rumah Sakit Umum Daerah Bangli - Budianingsih, Ni Nengah; Gumala, Ni Made Yuni; Tamam, Badrut (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
According to the 2023 Nutrition Installation Report at Bangli Regional General Hospital, food waste from three meals per day showed staple food (rice/porridge) had 22.4% leftovers, animal-based side dishes 24.5%, plant-based side dishes 29.8%, and vegetables 31%. These results exceed the Minimum Service Standard, which specifies food waste should be ≤20%. The study aims to determine the "Relationship between Patient Food Waste Based on Food Taste and Appearance at Bangli Regional General Hospital." This observational study with a cross-sectional design was conducted from April to May 2024. The sample size was 54, obtained through purposive sampling. Food waste was measured using the Comstock method, while taste and appearance were assessed using a questionnaire. Analysis used the Spearman test. Food waste occurred in 51 staple food samples (94.4%), 34 animal-based side dish samples (63%), 46 plant-based side dish samples (85.2%), 52 vegetable samples (96.3%), and overall food waste in 35 samples (64.8%). Regarding taste, 33 samples (61.1%) rated the food as "not tasty," and for appearance, 28 samples (51.9%) rated it as "appealing." The analysis showed a p-value of 0.000 (p 0.05), indicating a significant relationship between food taste and appearance with food waste.